Beta-gamma spectroscopy of the neutron-rich 150Ba. (16th April 2018) - Yokoyama, R; Ideguchi, E; Simpson, G S; Tanaka, Mn; Nishimura, S; Doornenbal, P; Lorusso, G; Söderström, P-A; Sumikama, T; Wu, J; Xu, Z Y; Aoi, N; et al.
Abstract: Excited states in the neutron-rich nucleus $^{150}$ Ba have been observed via ${\rm β}$ –${\rm γ}$ spectroscopy at the Radioactive Isotope Beam Factory, RIKEN Nishina Center. The $^{150}$ Ba ions were produced by the in-flight fission of a $^{238}$ U beam with an energy of 345 MeV/nucleon. The $E(2^{+})$ energy of $^{150}$ Ba was identified at 100 keV, which is the lowest known in the neutron-rich Ba isotopes. A ${\rm γ}$ -ray peak was also observed at 597 keV. A mean-field calculation with a fully 3D real space was performed and a static octupole deformation was obtained for the Ba isotopes. $K^{π}=0^{-}$ and $1^{-}$ excited states with significant octupole collectivity were newly predicted at around or lower than 1 MeV on the ground state of $^{150}$ Ba by a random-phase approximation calculation. The 597 keV ${\rm γ}$ ray can be interpreted as a negative-parity state, showing that $^{150}$ Ba may possess octupole collectivity.